2017
DOI: 10.1016/j.avb.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Method of homicide and severe mental illness: A systematic review

Abstract: There is limited research that has examined offense characteristics in homicides committed by individuals with mental illness and with differing psychiatric diagnoses. The aim of this systematic review is to synthesize previous findings of studies analyzing homicide behavior by mentally ill individuals, and reporting any associations between mental illness and method of homicide. We searched four databases (MedLine, PsychINFO, Web of Science and Embase), and identified 52 relevant articles for analysis. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 78 publications
(198 reference statements)
3
17
0
6
Order By: Relevance
“…Thus, it is possible that the offenders in our sample may be disproportionately composed of perpetrators of "abnormal homicide"a loosely defined term often used in reference to homicides committed by individuals who are afflicted with mental illness or who commit suicide in conjunction with homicide (Coid, 1983;Simpson, Skipworth, Mckenna, Moskowitz, & Barry-Walsh, 2006). Indeed, that supposition is supported by the association between mental illness and close-contact methods of homicide (Abreu Minero et al, 2017), combined with the reduced likelihood of clearance in cases that involve distant-contact methods such as shooting .…”
Section: Strengths Limitations and Sources Of Bias And Confoundingmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, it is possible that the offenders in our sample may be disproportionately composed of perpetrators of "abnormal homicide"a loosely defined term often used in reference to homicides committed by individuals who are afflicted with mental illness or who commit suicide in conjunction with homicide (Coid, 1983;Simpson, Skipworth, Mckenna, Moskowitz, & Barry-Walsh, 2006). Indeed, that supposition is supported by the association between mental illness and close-contact methods of homicide (Abreu Minero et al, 2017), combined with the reduced likelihood of clearance in cases that involve distant-contact methods such as shooting .…”
Section: Strengths Limitations and Sources Of Bias And Confoundingmentioning
confidence: 95%
“…Moreover, an association between deliberate self-harm and violent criminalityindependent of concurrent psychiatric disorderhas been shown in a large cohort study from Sweden (Sahlin et al, 2017). Further, a recent review has examined the association between type of mental illness in homicide offenders and the means of violence used to perpetrate their lethal acts (Abreu Minero, Barker, & Bedford, 2017); the authors found significant associations between schizophrenia/delusional disorder and sharp violence, and between mood disorders and asphyctic violence.…”
Section: Mental Disorder Violence and Homicidementioning
confidence: 99%
“…Currently, there is a widespread interest in the study of homicide, not only by international organizations, such as the UNODC and the World Health Organization [2,3,4,5], but also by the academic world, where numerous studies have been conducted in an attempt to extend the knowledge of this criminal phenomenon from diverse perspectives (socio-cultural development factors, psychopathological, neuropsychological) [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the choice of the weapon used to carry out a homicide depends on many variables, such as the context in which the murder takes place and the social availability of the instrument used [3,36]. Thus, homicide by firearms is more frequent in the USA and Italy, as a result of less restrictive gun laws and homicides involving organized crime, respectively [36][37][38]. For parricide, firearms are quoted as the main weapon used in the studies carried out in the USA [39].…”
Section: Discussionmentioning
confidence: 99%